Foreign direct investment location and trade dynamics in Viet Nam after the US-PRC trade dispute - Yesim Elhan-Kayalar; Konstantin Kucheryavyy; Manabu Nose; Yasuyuki Sawada; Ruo Shangguan; Nguyen Thanh Tung (Asian Development Bank (ADB), 2024)
In developing economies, foreign direct investment (FDI) plays a crucial role by providing resources that facilitate participation in international trade and support economic development. Focusing on Viet Nam as a case study, this research aims to quantify the distributional effects of the United States-People's Republic of China trade dispute across different regions in Viet Nam. By utilizing detailed firm-level and customs data, we demonstrate that FDI in Viet Nam is geographically concentrated in the northern, central, and southern regions. Access to road and port networks significantly influences the choice of FDI locations. Furthermore, we highlight the important role that the foreign affiliates of multinational firms from East Asia and the United States have played in reshaping Viet Nam's trade flows in the aftermath of the trade dispute between the United States and the People's Republic of China. This study sheds light on the interplay between transport infrastructure, FDI, and international trade.
Keywords: R40; R41; F10; F13; F14; 330; trade; ports; roads; US-PRC trade dispute; Viet Nam; PRC